Hubungan pelaksanaan fungsi perawatan kesehatan keluarga Dengan status gizi balita - Sari, Indah Sintia; -, Agrina -; HD, Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to know the relationship between the implementation of family health care function to nutritional status of children aged under five years in Padang Bulan village, Pekanbaru. This research was quantitative research design with descriptive cross sectional correlational approach. The total of sample were 82 mothers who have children and conducted by accidental sampling. The instrument used weight scale (Kg) ang height scale (Cm) which interpreted by standard of WHO-NCHS (2005) as the variable of nutritional status. The instrument used the questionnaire to measure the function of family health care which had been tested the validity and reliability. This research used univariate analyse to determine the distribution of frequencies and bivariate analyse Kolmogorof Smirnov. The result of this study showed that most of children had good nutritional status and most of mothers had implemented the family health care functions excellently. It showed, there is a relationship of the  implementation of family health care functions to nutritional status of children aged under five years (p value= 0,014). Based on this result, it is recommended to each mother to improve the nutritional status of children aged by doing the function of health family care well. Keyword: the implementation of family health care function, nutritional status the children aged under five years